The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/awwa.1753
|View full text |Cite
|
Sign up to set email alerts
|

Beware of Legionella in Water Distribution Systems

Abstract: Having completed the inaugural WaterQuality Matters column series focusing on the theme "Hot Topics in Water Quality," initiated in the April 2019 issue of Journal AWWA, the AWWA Water Quality and Technology Division's committees extend the conversation in this recurring column by expounding on a common question, "What keeps you up at night?" The column in this issue has been prepared by the Water Quality Laboratory Committee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In 24% of cases (155/645), borderline contamination (over 100 but less than 1000 CFU/L) was found, indicating the need for careful surveillance of the phenomenon. As research has shown, keeping Legionella under control in a water distribution system always requires an optimal systematic schedule of disinfection, water management, nutrient limitation, and temperature control [16,24]. In this regard, it should be noted that the decrease in the positivity rate observed in our study is attributable to the effectiveness of the sanitization protocols put in place.…”
Section: Discussionmentioning
confidence: 57%
“…In 24% of cases (155/645), borderline contamination (over 100 but less than 1000 CFU/L) was found, indicating the need for careful surveillance of the phenomenon. As research has shown, keeping Legionella under control in a water distribution system always requires an optimal systematic schedule of disinfection, water management, nutrient limitation, and temperature control [16,24]. In this regard, it should be noted that the decrease in the positivity rate observed in our study is attributable to the effectiveness of the sanitization protocols put in place.…”
Section: Discussionmentioning
confidence: 57%
“…A well‐developed QA/QC program supports the production of reliable data, which in turn supports good decision‐making throughout a utility (Jarvis & London‐Exner 2019). Further, utilities should have a clear communications plan so that data can be reported within the utility and/or to the public quickly and efficiently, especially during an emergency (Malz 2021).…”
Section: Laboratory Accreditation Guides Best Practicesmentioning
confidence: 99%
“…3 Recently, the rate of occurrence of confirmed legionellosis in the United States has been rising, from approximately 1 case per 100,000 people in 2010 to 3 cases per 100,000 people in 2018. 4 Furthermore, the report of the National Academies of Sciences, Engineering, and Medicine (NASEM) on the management of Legionella in water systems estimates that true incidence of both inpatient and outpatient Legionnaire's disease could have been as high as 20−27 cases per 100,000 people in 2020. 2 Opportunistic pathogens (OPs), such as Legionella spp., Mycobacterium spp., Pseudomonas aeruginosa, and Acanthamoeba, are removed or inactivated during drinking water treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It also can cause a milder, influenza-like illness known as Pontiac Fever . Recently, the rate of occurrence of confirmed legionellosis in the United States has been rising, from approximately 1 case per 100,000 people in 2010 to 3 cases per 100,000 people in 2018 . Furthermore, the report of the National Academies of Sciences, Engineering, and Medicine (NASEM) on the management of Legionella in water systems estimates that true incidence of both inpatient and outpatient Legionnaire’s disease could have been as high as 20–27 cases per 100,000 people in 2020…”
Section: Introductionmentioning
confidence: 99%